Parental Academic Support in Online and Modular Learners Amidst Pandemic: A Comparative Study - M.C Palma; T.N.V Escucha; Z.B Distor; B.V Tuyao; A. Malaco; J. Estrellan (Indonesian Journal of Community and Special Needs Education, 2021)
This study aims to determine how the impact of the COVID pandemic on the education system so that it changes learning patterns in daily life in the form of online and modular learning. How the attitude of parents in dealing with changes in educational normality faced by children as students is the focus of this research. In this study, parents were considered as an integral part of this survey due to their direct contact with learners. The results showed that the variables affected a parent's ability to actively participate in their child's education during the pandemic. The variables were influenced by (1) the parental role construction which is shaped by the beliefs, perception, and experiences of the parent; (2) the socioeconomic status of the parent which influences the skill, knowledge, energy, and time availability of the parent; (3) the invitation of parents by the teachers and schools to be active participants in the education of their children during the pandemic; (4) and the self-efficacy and confidence derived by the parent from being an active participant. We collected data from our respondents in the form of a survey, in which the data, through a Likert scale, were separated based on what form of modality the respondent is undertaking and they were analyzed by finding its mean and difference between the two media of education. The findings revealed that the major concern of the parents was related to children facing the problems due to sudden school closure and a complete lockdown on social gatherings. To address these challenges, schools have played a phenomenal role in flipping the conventional model of teaching and learning. However, phenomena have not been as easy as they may seem. Many teachers had to speedily overcome camera consciousness and be able to deliver 'live' classes. Moreover, parents have adapted quickly to address the learning gap that has emerged in their children’s academic lives in these challenging times. Home learning has emerged as a substitute to the conventional schooling methods, which should be made effective to provide essential learning skills to children at home using the limited available resources. The limitations remain like how parents with different educational backgrounds will follow through the instructions; therefore, online schooling to support home learning can be a go-to strategy where teachers deliver education online. This research provides parents with an overview of how their support has affected their children's academic performance so far, as well as provides them with knowledge about their shortcomings in supporting their children's education during the pandemic.